Perceptions of Latin American immigrant families in Spain about the educational field: a dialogic-decolonial turn - Serrano Manzano, Bianca Fiorella (2017)
The dialogic turn, characteristic of today's complex society, is changing the way how we work in the socio-educational field with people at risk of social exclusion. This change has extended to its research. Latin American immigrant population in Europe, especially women and children, is part of this group. From this principle, the study analyzes the communicative processes of Latin American families in educational areas, reaching six categories of analysis and distinguishing whether these interactions generate exclusionary or transformative dynamics. Thirty people from six countries in Latin America participated. It begins from a qualitative-critical communicative methodology, as a way of optimizing options to overcome the inequalities produced by the western neoliberal thought about decolonialism